The effects of glove fit on task performance and on the human operator - Stack, Jessica Danielle (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2010)
The hand is one of the most complex of all of the anatomical structures in the human body. It has been found that hand injuries are among the most frequent injuries that occur to the body, predominantly during industrial activities. It has therefore been concluded that more research is needed into protective factors, such as glove use. The design features of a glove emphasise either protection or performance. There is often a trade-off between increased safety and performance capability when donning gloves. It has been determined that gloves which are fitted and comfortable for the worker may provide the best compromise between protective functions and decreased performance. This investigation aimed to assess the influence of glove fit on the performance attributes of industrial tasks, as well as on the responses of the human operator. Glove fit was analysed as 35 male participants donned three different glove sizes during each test, including a best-fitting glove, a glove one size smaller than best-fitting, and a glove one size larger than best-fitting. For each glove size, gloves of two differing materials were tested, namely nitrile and neoprene. A barehanded condition was also tested, totalling seven gloved/barehanded conditions for each test. The seven conditions were assessed in a laboratory setting in a battery of tests. This consisted of components of task performance, including maximum pulling and pushing force, maximum torque, precision of force, tactility, speed and accuracy and dexterity. The performance responses were recorded, as well as participants' perceptual responses using the Rating of Perceived Exertion scale, and muscle activity. Six muscles were selected: Flexor Digitorum Superficialis, Flexor Pollicus Longus, Extensor Carpi Ulnaris, Extensor Carpi Radialis, Flexor Carpi Ulnaris and Flexor Carpi Radialis. The results revealed that glove fit does affect certain spects of performance, and influences human operator responses for selected task components. Furthermore, discrepancies were distinguished between orking barehanded and working with an optimally fitted glove. There was also a glove material effect established. Overall, it was found that muscle activity when exerting maximum force in a pushing and pulling direction was optimal with the nitrile glove material. Maximum torque performance was enhanced with the use of a best-fitting glove, as compared with an ill-fitting glove or barehanded work. Force precision was preferable when barehanded, as opposed to the tactility task which rendered optimal results with a best-fitting glove. The same was found for speed and accuracy results, as glove fit appeared to have no effect on performance, but performance was improved when participants were barehanded. Dexterity performance was the most conclusively influenced by the conditions, resulting in barehanded performance being optimal. However, should a glove be necessary for a given task, an optimally-fitted glove which is of a thinner material would be recommended. It is necessary to distinguish the performance components of a task within industry and select the most appropriate glove for optimal performance and the least risk of overexertion.
Keywords: Hand -- Anatomy; Hand -- Wounds and injuries; Hand -- Care and hygiene; Gloves; Safety education, Industrial; Human-machine systems; Industrial safety; Industrial accidents